On Best Approximation and Best Coapproximation: Tulsi Dass Narang, Sahil Gupta - Team, Support (Thai Journal of Mathematics, 2016)
In this paper, the concept of best coapproximation is employed to prove various characterizations of proximinal, coproximinal, Chebyshev and co-Chebyshev subspaces. The continuity properties of metric projection, metric coprojection and related maps have also been discussed. The underlying spaces are normed linear spaces and metric linear spaces.